Multiply both sides of the equation by 6 to eliminate the denominators:
\[
6 \left( \frac{3r + 5}{6} + 1 \right) = 6 \left( \frac{4r + 3}{3} \right).
\]
Step 2: Simplify both sides
Simplify the left and right sides of the equation:
\[
(3r + 5) + 6 = 2(4r + 3).
\]
Step 3: Expand and combine like terms
Expand the right side and combine like terms on the left side:
\[
3r + 5 + 6 = 8r + 6.
\]
\[
3r + 11 = 8r + 6.
\]
Step 4: Solve for \( r \)
Subtract \( 3r \) from both sides and then subtract 6 from both sides:
\[
11 = 5r + 6.
\]
\[
5 = 5r.
\]
Divide both sides by 5:
\[
r = 1.
\]